(untitled) (مجلة إحالات, 2026)
We seek through this research paper to talk about the Corona pandemic and its manifestations in the short story through an exemplary study of the story (Corona Kills Mary) by the writer Saleh Mabrouki, who tried to deal with this epidemic based on his broad imagination, and based on a realistic experience. It was a painful experience that global societies experienced, and its bitterness was felt by the psychological, material, social and economic effects it left on the individual and society. From here, a central problem can be formulated for this topic, which is represented in the search for the tragic dimensions of the Corona pandemic in the short story, and what are the anecdotal foundations that the narrator relied on in formulating his imaginary story, and what are the aesthetic ingredients in the story (Corona kills Mary)? And what is the cognitive framework and the intellectual and scientific starting points from which Arab storytellers set out to dissect this new epidemic phenomenon?